Is It Feasible to Implement Enteral Nutrition in Patients With Enteroatmospheric Fistulae? A Single‐Center Experience. (11th June 2014) - Yin, Jianyi; Wang, Jian; Yao, Danhua; Zhang, Shaoyi; Mao, Qi; Kong, Wencheng; Ren, Lele; Li, Yousheng; Li, Jieshou
Abstract : Background: Published experience in feeding patients with enteroatmospheric fistulae is scarce. This study aimed to determine if enteral nutrition (EN) could be safely delivered in the presence of enteroatmospheric fistula. Materials and Methods : This is a retrospective descriptive study from a major fistula treatment center in China. Medical records of patients who developed enteroatmospheric fistulae in the open abdomen after abdominal trauma were reviewed. The timing of initiation and achievement of full strength (25 kcal/kg/d) EN after enteroatmospheric fistula were noted, as well as the incidence of feeding‐associated complications and weaning of parenteral nutrition (PN). The outcomes of open abdomen and enteroatmospheric fistula were also noted. Results : Nine patients were included in this study. EN was successfully implemented in all patients. The median timing of initiation and achievement of full strength of EN after enteroatmospheric fistula was 9 (interquartile range [IQR], 3–22) and 27 (IQR, 22–43) days, respectively. Feeding‐associated complications developed in 1 (11.1%) patient. All patients were liberated from PN at hospital discharge. Split‐thickness skin grafting was performed in all patients, of whom 5 underwent successful delayed abdominal closure, and 4 were awaiting definitive closure. Repair or resection of enteroatmospheric fistula occurred in 8 (88.9%) patients. Conclusion : This study showed that EN could be safely implemented in patients with enteroatmospheric fistulae without complicating the treatment of open abdomen and enteroatmospheric fistula.